The Effects of Public Sector Management and Institutions on Stock Market Development in Sub- Saharan Africa - Gideon Mensah; Anthony Kofi Osei-Fosu; Grace Nkansah Asante (Cogent Economics & Finance, 2022)
Recently, sub-Saharan Africa (SSA) stock markets have received an exceptional attention as a market of hope and future. Hence, policy-makers, investors and financial analysts have been striving to ameliorate the factors that are detrimental to stock market development in SSA. Given this, the primary focus in literature has been based on the role that institutions play in influencing stock market development in SSA. Hence, this study employed fixed and random effect estimations technique on a balanced panel data of six (6) selected SSA countries to explore the impact of public sector management and institutions on stock market development in SSA for the period 2005-2018. This study found that, on average, countries with quality public sector management and institutions have been able to improve on their stock market development compared with countries without quality public sector management and institutions. In disaggregating the impact of public sector management and institutions into West and East countries in SSA, the study further demonstrated that public sector management and institutions enhance stock market development in these countries in SSA. However, we found that the effect of public sector management and institutions is insignificant in the East Africa communities (EACs). Based on these results, the study recommends that governments in SSA should put in place stringent measures that seek to enhance public sector management and institutions within SSA countries.
Keywords: 330; Public sector management and institutions; stock market development; subSaharan Africa; fixed and random effect